2020
DOI: 10.1590/1806-9061-2017-0700
|View full text |Cite
|
Sign up to set email alerts
|

Potential Value of Using Insect Meal As an Alternative Protein Source for Japanese Quail Diet

Abstract: A feeding trial was conducted to determine the potential value of replacing 100 % of meat and bone meal (MBM) ingredient as the major animal protein source in Japanese quail diets by 50% and 100% of insect meal derived from S. littoralis Larvae. A total of 360, 7 daysold quail chicks, were randomly divided into three equal groups (120 chicks) with three replicates each. They were offered three different diets 1, 2 and 3, respectively. The Diet 1 contained MBM only as a major source of animal protein, diet 2 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 16 publications
6
8
0
1
Order By: Relevance
“…It was also mentioned by Kareem et al [31] that the incorporation of black soldier fly larvae to broiler diets up to 10% had no negative effect in their growth performance under humid tropical environment. In addition, no adverse effects on growth performance, carcass characteristics, hematological and serum biochemical indices in growing Japanese quail when meat and bone meal replaced with Spodoptera littorails in their diets [35]. It was claimed by Neumann et al [36] that partly adding defatted insects meal of Hermetia illucens larvae in broiler diets -26% and 22% in starter and grower phase, respectively -were acceptable.…”
Section: Insects and Wormsmentioning
confidence: 99%
“…It was also mentioned by Kareem et al [31] that the incorporation of black soldier fly larvae to broiler diets up to 10% had no negative effect in their growth performance under humid tropical environment. In addition, no adverse effects on growth performance, carcass characteristics, hematological and serum biochemical indices in growing Japanese quail when meat and bone meal replaced with Spodoptera littorails in their diets [35]. It was claimed by Neumann et al [36] that partly adding defatted insects meal of Hermetia illucens larvae in broiler diets -26% and 22% in starter and grower phase, respectively -were acceptable.…”
Section: Insects and Wormsmentioning
confidence: 99%
“…This trend is contrary to that of Marareni and Mnisi [ 40 ], who found a reduction in the values of these components in their work on the study of growth performance, serum biochemistry, and meat quality in Jumbo quails given a diet comprising mopane worm meal ( Imbrasia belina ). However, this is not the case for the work of Cullere et al [ 32 ], Hatab et al [ 41 ], and Woods et al [ 42 ], who fed birds with black soldier fly or Hermetia illucen larvae collected from different substrates and noted an increase in the values of the carcass proportions.…”
Section: Discussionmentioning
confidence: 98%
“…The adverse effects of exposing to heat stress on performance, physiological activity, nutrient absorption, digestion, blood circulation, respiration ,consumption and utilization of food and sensitivity against several diseases etc. are well reviewed by (Sayed et al 2019;Hatab et al 2020). In further study conducted by (Sahin et al 2009; Kang and Shim 2021) reported the role of stress factors in inducing the expression of Heat shock proteins in the Japanese quail.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, more recent researches have evaluated the potential value of insect meal as poultry feed derived from another insect species. New avenues were opened for the utilization of the common cutter biller, Spodoptera littoralis larvae and/or the peach fruit y, Bactrocera zonata as sources of protein as feed (Basiouny et al 2016;Sayedet al 2019;Hatab et al 2020). B. zonata could play an prominentrole as feed because it has short life cycles and can be reared on a large scale using low cost material as feed substartes like other fruit y species Parker (2005).…”
Section: Introductionmentioning
confidence: 99%